2005
DOI: 10.1021/ma050570p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thermoresponsive Graft Copolymers of NIPAAm and 2-Alkyl-2-oxazolines by the “Grafting from” Method

Abstract: New thermoresponsive graft copolymers were synthesized by the cationic ring-opening polymerization of 2-methyl-2-oxazoline (MeOxa) or 2-ethyl-2-oxazoline (EtOxa), initiated by the random copolymers of chloromethylstyrene (CMS) and N-isopropylacrylamide (NIPAAm) using the “grafting from” method with a yield of 66−94%. The polymers were characterized by NMR, GPC, and DSC, and the conformational transition (lower critical solution temperature, LCST) of macroinitiators and graft copolymers was determined by the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 40 publications
2
63
0
10
Order By: Relevance
“…Voit et al investigated graft copolymers with thermoresponsive poly(NIPAM-stat-chloromethylstyrene) backbones and hydrophilic poly(2-alkyl-2-oxazoline) side-chains. The phase transition temperatures were found to increase with increasing number and length of the side-chains [33].…”
Section: Thermoresponsive Poly(2-oxazoline)s In Aqueous Solutionmentioning
confidence: 95%
“…Voit et al investigated graft copolymers with thermoresponsive poly(NIPAM-stat-chloromethylstyrene) backbones and hydrophilic poly(2-alkyl-2-oxazoline) side-chains. The phase transition temperatures were found to increase with increasing number and length of the side-chains [33].…”
Section: Thermoresponsive Poly(2-oxazoline)s In Aqueous Solutionmentioning
confidence: 95%
“…Phase transition could be altered not only via side-chain composition or structure, but also by hydrolysis of the methyl ester groups and subsequent carboxylic acid functionalization. Tailoring of the polymer properties was also reported to be feasible by the parameters macroinitiator and hydrophilic/hydrophobic segments [104]. An increasing quantity of chloromethylstyrene in the backbone lowered the LCST, while an increasing content of pMeOx or pEtOx (relative to the backbone) raised the transition temperature.…”
Section: Grafting From Heteropolymer Side-chainsmentioning
confidence: 99%
“…Each cycle lasts only several minutes. It was reported that PNIPAAm [55] shows its LCST at 32°C in aqueous solution. The hydrogen bond is formed between the water and N-isopmpylacrylamide group when the temperature under the LCST, and it will display the hydrophilic properties.…”
Section: The Responsive Switch Of Sio 2 /P (7-6-ac)-b-pnipaam Compositesmentioning
confidence: 99%